Studi Literatur Basis Data SQL dan NoSQL - Widya Nita Suliyanti (Sekolah Tinggi Teknik - PLN, 2019)
With the increasing need to store large amounts of unstructured and semi-structured data, the database that used to be mostly using SQL technology, began using the NoSQL database. The purpose of this paper is to conduct a literature study of the characteristics, advantages and disadvantages of SQL and NoSQL databases. This literature study shows that there are differences in SQL databases and based on characteristics (ACID for SQL vs. BASE and CAP for NoSQL); data model (relational for SQL and key-value for NoSQL); data structure (structured for SQL and non- or semi-structured for NoSQL); process (subquery, join and grouping / aggregation and complex queries faster only for SQL); and the number of servers used (single large server for SQL and multiple multiple levels for NoSQL). A literature review for further SQL and NoSQL applications is needed in the future.